Hardy-Sobolev spaces of higher order associated to Hermite operator - Jizheng Huang; Shuangshuang Ying (Communications in Analysis and Mechanics)
Let $ L = -Δ+|x|^2 $ be the Hermite operator on $ \mathbb R^{d} $, where $ Δ $ is the Laplacian on $ \mathbb R^{d} $. In this paper, we will consider the Hardy-Sobolev spaces of higher order associated with $ L $. We also give some new characterizations of the Hardy spaces associated with $ L $.